2015
DOI: 10.1016/j.ijimpeng.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of target thickness on the ballistic performance of ultra high molecular weight polyethylene composite

Abstract: The ballistic performance of thick ultra-high molecular weight polyethylene (UHMW-PE) composite was experimentally determined for panel thicknesses ranging from 9 mm to 100 mm against 12.7 mm and 20 mm calibre fragment simulating projectiles (FSPs). Thin panels (<~10 mm thick) were observed to undergo large deflection and bulging, failing predominantly in fibre tension. With increased thickness the panels demonstrated a two-stage penetration process: shear plugging during the initial penetration followed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 24 publications
6
112
0
Order By: Relevance
“…Recent studies by Karthikeyan and Russell [13] using a spherical projectile and by Nguyen et al [14] using fragment simulating projectiles (FSP) confirmed the existence of progressive penetration before the laminate ballistic limit was attained. All these studies indicate the penetration of these materials occurs in two stages schematically illustrated in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies by Karthikeyan and Russell [13] using a spherical projectile and by Nguyen et al [14] using fragment simulating projectiles (FSP) confirmed the existence of progressive penetration before the laminate ballistic limit was attained. All these studies indicate the penetration of these materials occurs in two stages schematically illustrated in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…The effect of sample thickness on the ballistic performance has been investigated by various researchers [2,30,31]. Gellert et al [2] examined the effect of target thickness on the ballistic perforation of glass fibre reinforced plastic composites.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies need to be performed with multiple projectiles and areal densities to continue to elucidate the ARL X Hybrid behavior for modeling efforts. In addition, the effect of curvature also needs to be explored, as previous research has shown that blunt deformation is more severe due to helmet form compared to flat plate of the same materials design [39,40].…”
Section: Discussionmentioning
confidence: 99%